Estimation and control of cooperative aerial manipulators for a payload with an arbitrary center-of-mass - Lee, Hyeonbeom; Kim, Uikyum (Sensors, 2021)
This paper presents an integrated framework that integrates the kinematic and dynamic parameter estimation of an irregular object with non-uniform mass distribution for cooperative aerial manipulators. Unlike existing approaches, including impedance-based control which requires expensive force/torque sensors or the first-order-momentum-based estimator which is weak to noise, this paper suggests a method without such sensor and strong to noise by exploiting the decentralized dynamics and sliding-mode-momentum observer. First, the kinematic estimator estimates the relative distances of multiple aerial manipulators by using translational and angular velocities between aerial robots. By exploiting the distance estimation, the desired trajectories for each aerial manipulator are set. Second, the dynamic parameter estimation is performed for the mass of the common object and the vector between the end-effector frame and the center of mass of the object. Finally, the proposed framework is validated with simulations using aerial manipulators combined with two degrees-of-freedom robotic arms using a noisy measurement. Throughout the simulation, we can decrease the mass estimation error by 60% compared to the existing first-order momentum-based method. In addition, a comparison study shows that the proposed method satisfactorily estimates an arbitrary center-of-mass of an unknown payload in noisy environments.
Keywords: Arbitrary center-of-mass; Centers-of-mass; Cooperative aerial manipulation; Dynamic parameter estimations; Dynamics uncertainties; First order; Integrated frameworks; Kinematics and dynamics; Kinematics parameters; Parameters estimation; Biomechanical Phenomena; Computer Simulation; Mechanical Phenomena; Motion; Arbitrary center-of-mass; Cooperative aerial manipulation; Dynamic uncertainty; Parameter estimation